Voluntary Servitude in Digital Capitalism: A Synthesis of Frommian and Fuchsian Thought on Instagram Influencer Activities - Grace Heidy Jane Amanda Wattimena; Andre Ikhsano; Frengki Napitupulu (CV. Social Politic Genius (SIGn), 2026)
The freedom of Instagram influencers within the structure of platform capitalism represents a structural contradiction that can be examined as voluntary servitude. This study aims to synthesize Erich Fromm’s critical psychology and Christian Fuchs’s political economy of digital media to explain how structural unfreedom is accepted as a form of autonomy by digital actors. This study uses a qualitative method with a literature research design through a conceptual-critical approach, without direct empirical testing of influencer subjects. The synthesis constructs a theoretical abstraction called the Dialectical Model of Freedom in Digital Capitalism. This model holds that the subject’s release from traditional authority yields negative freedom, but not necessarily positive freedom. In the context of achievement society, the post-emergence situation from primary bonds may encourage psychological escape through automaton conformity, which forms the pseudo self. This psychic submission is then converted by platform capitalism into a prosumer commodity through the mechanism of playbour. Aspirational labor, visibility labor, precarious employment, digital Taylorism, visibility game, and shadowbans show that creative autonomy is conditioned by the interests of visibility and value extraction. This study concludes that voluntary servitude should be understood as an analytical category for explaining subjective acceptance of digital exploitation structures. Its implications require digital communication studies to strengthen critical digital literacy, protect digital workers, improve transparency in algorithmic governance, and democratize platform infrastructure.